(untitled) - Murray, Julie (Edina (United States), 2006)
This book talks about history of Pennsylvania. It was one of the 13 original colonies. This states is home to the Liberty Bell and Independence Hall.
Keywords: Pennsylvania,Pennsylvania; Juvenile literature,Văn học tuổi vị thành niên